Simple method to assess stability of immobilized peptide ligands against proteases - Giudicessi, Silvana Laura (2017)
Although peptides are used as affinity chromatography ligands, they could be digested by proteases. Usually, peptide enzymatic stability is evaluated in solution, which differs from the resin-bounded peptide behavior. Furthermore, the study of the degradation products requires purification steps before analysis. Here we describe an easy method to evaluate immobilized peptide stability. Sample peptides were synthesized on hydroxymethylbenzamide-ChemMatrix resin. Peptidyl-resin beads were then incubated with solutions containing proteases. Peptides were detached from the solid support with ammonia vapor and analyzed by MALDI and ESI mass spectrometry, allowing the detection of the whole peptide as well as their C-terminal degradation products. The method allowed a fast evaluation of peptide ligands stability in solid phase towards proteases that may be present in the crude sample before their use in affinity chromatography.